Role of microfinance Institutions for sustainable development goals in Bangladesh - Uddin, Md Nazim; Hamdan, Hamdino; Che Embi, Nor Azizan; Kassim, Salina; Md Saad, Norma (2019)
The purpose of this paper is to explore the Microfinance Instruments in achieving the Sustainable Development Goals (SDGs) in Bangladesh. Propose a conceptual model along with exploring the contributions in attaining SDGs to fill up the gap. The methodology of this study based on secondary data includes existing relevant literature and annual reports of conveniently sampled 20 microfinance institutions in Bangladesh. The findings of this study show that microfinance institutions have a broader scope to attain Sustainable Development Goals through their various investment modes. The study categorises the microfinance instruments into large parts which are poverty reduction, end hunger, good health, equality education, clean water, sanitation energy, gender equality, empowering women, and financing which have a positive effect to the real sector of the sustainable economy that will lead towards achieving SDGs. The Microfinance institutions are continuing their efforts in attaining Sustainable Development Goals through their various products. With growing the potentiality, microfinance has both direct and indirect impacts on ensuring economic development, environmental sustainability, and social inclusion by creating employment opportunity, spreading knowledge and skills, making self-dependent, protecting from adverse effects. The paper also tries to put recommendations to reduce the challenges of microfinance acting as impediments to achieving the SDGs.